2012
DOI: 10.2147/ijgm.s33549
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-positive ileal extraosseous plasmacytoma containing plasmablastic lymphoma components with CD20-positive lymph node involvement

Abstract: We report a case of Epstein–Barr virus (EBV)-positive ileal extraosseous plasmacytoma containing plasmablastic lymphoma components with CD20-positive lymph node involvement. A 34-year-old healthy Japanese male developed intussusception due to an ileal plasmacytoma. The lesion was positive for EBV-encoded small nuclear RNA in in situ hybridization, with the surrounding lymph nodes showing the expression of CD20. Tumor cells in the ileal and lymph node lesions contained high-grade malignant features compatible w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The head and neck and the gastrointestinal tract were the most common sites. Little information is available in the literature regarding therapy, follow‐up, or survival, with the exceptions of a case reported by Saito et al . and the cases that we report here.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…The head and neck and the gastrointestinal tract were the most common sites. Little information is available in the literature regarding therapy, follow‐up, or survival, with the exceptions of a case reported by Saito et al . and the cases that we report here.…”
Section: Discussionmentioning
confidence: 63%
“…EBV‐positive plasmacytomas in immunocompetent hosts have been described in the literature, and are summarized in Table . Including the four cases that we report here, a total of 11 cases of EBV‐positive plasmacytoma have been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Although it has been suggested that PBL may occur as a high-grade transformation from a pre-existing plasmacytoma following EBV infection, this concept has not been well established and definitive proof is lacking. 3,4 In December 2011, a 74-year old man presented for a right maxillary sinus solitary mass, infiltrating the oral cavity. Histological examination of the bioptic specimen showed a uniform proliferation of plasma cells with abundant cytoplasm, round eccentrically located nuclei and clock-face chromatin without nucleoli ( Figure 1A).…”
mentioning
confidence: 99%